Faktor-faktor Loyalitas Generasi Z terhadap Mobile Banking yang dilengkapi Kecerdasan Buatan : Bank Syariah di Indonesia - Lestari, Fitri; Indarta, Ahmad (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract Islamic banks must be able to compete in the digital era along with technological advances in the financial industry. Islamic banks that are relatively new are often considered less popular and less experienced, hence they must take note of the growth and expansion of customer loyalty, especially in mobile banking services equipped with assistive intelligence (AI) to achieve competitive advantage. The aim of this research was to identify the elements that motivate Generation Z’s allegiance to AI-powered Islamic mobile banking. Generation Z residents of Surakarta made up the study’s population. Sampling used purposive sampling with 100 respondents. The approach used was quantitative and analyzed using IMB SPSS version 2023. The results of the study showed that service quality, trust, and satisfaction were determining factors for the loyalty of generation Z to Islamic mobile banking equipped with artificial intelligence (AI). Meanwhile, customer loyalty to Islamic mobile banking among Generation Z was not significantly impacted by religiosity. With this study, it is hoped that Islamic banks can increase customer loyalty by developing the determining factors for customer loyalty. Keywords : Customer loyalty, service quality, trust, satisfaction, religiosity